THE IMPORTANCE OF ENVIRONMENTAL EDUCATION IN RURAL AREAS AND AT THE SAULO MAIA MUNICIPAL ELEMENTARY SCHOOL, IN THE CORREDOR SETTLEMENT, REMÍGIO-PB - Silene Leite, Patrícia; Ferreira Ramos, Raider; Selma de Araújo Pinto Santos, Maria; Fabiana Marques Cista Dias, Carla; Francis Marcos Bernal, Ira; Edith Marcos Bernal, Susan; Roger Alves de Oliveira, Elton; Nathan Epaminondas de Amaral, Tuany; Bezerra do Nascimento, Daniel; Fabiana Marques Cista Dias, Carla (Revista Gênero e Interdisciplinaridade, 2026)
This paper presents a participatory diagnosis conducted with residents of a settlement to evaluate the quality of education and local infrastructure. Using a rating methodology (0 to 10), the settlers analyzed areas such as people, services, society, and resources. The results indicated good participation from community leaders (8.5), but pointed to critical deficiencies in school infrastructure and medical care. Although government programs have improved the quality of life, bureaucracy still hinders access to credit. The ultimate goal is to use this data to conduct pedagogical workshops that integrate theory and practice, strengthening the bond between the community and the school.